The impact of COVID-19-related mental health issues on menstrual cycle characteristics of female healthcare providers. - Takmaz, Taha; Gundogmus, Ibrahim; Okten, Sabri Berkem; Gunduz, Anil (My University, 2021)
To investigate the association between menstrual cycle regularity in healthcare providers and COVID-19 pandemic-related anxiety, depression, stress.

A cross-sectional study was conducted by administrating online questionnaires to female healthcare workers in Turkey. Women aged 18-40 years with regular menstrual cycles for more than 1 year before the beginning of the pandemic were included in the study and they were divided into two groups according to menstrual cycle regularity during the pandemic. The questionnaires included sociodemographic characteristics, medical and reproductive history, lifestyle information of participants, COVID-19 Stress Scales (CSS), and a short version of the Depression Anxiety Stress Scale (DASS-21).

A total of 952 women were included in the study, 679 had regular menstrual cycles, and 273 had irregular menstrual cycles. The prevalence of irregular menses among Turkish women healthcare workers aged 18-40 years was 28.7%. The CSS subdimensions and total scores were significantly higher in the irregular menstruation group than in women with regular menstruation (p < 0.001). The DASS-21 depression, anxiety, and stress subdimensions were likewise significantly higher in women with irregular menstruation (p < 0.001). Besides, both the univariable and the multivariable logistic regression results showed the relationship between irregular menstruation and CSS total score.

The current study showed the association between the COVID-19 pandemic-induced anxiety, perceived stress, depressive symptoms, and increased prevalence of menstrual cycle irregularity among healthcare providers.
Keywords: COVID-19; anxiety; depression; healthcare providers; menstrual cycle irregularity; stress